Perubahan Tradisi Marpege-Pege Masyarakat Batak Angkola di Padangmatinggi Lestari, Sumatera Utara - Ahmad Rajab Siregar (Haluan Sastra Budaya, 2025)
Batak angkola is one of the Batak tribes that settled in Padangsidimpuan and surrounding areas. This region is divided into several villages, one of which is Padangmatinggi Lestari. The Angkola Batak community in Padangmatinggi Lestari has unique traditions and is still preserved today, including marpege-pege. In general, this tradition is only carried out at the groom's house. In Padangmatinggi Lestari, the marpege-pege tradition has changed in its implementation. This study aims to analyze changes in the marpege-pege tradition of the Angkola Batak community in Padangmatinggi Lestari. The method used in this research is qualitative research method. The approach used is a semiotic approach with the challenge and response theory coined by Arnold J. Toynbee. The results of this study show that there are two changes in the marpege-pege tradition in Padangmatinggi Lestari. First, the marpege-pege tradition may be held by the bride-to-be. This change originated from an incident experienced by a traditional leader in Padangmatinggi Lestari who did not have a son. As a result, he could not hold this tradition when his daughter was getting married.  This incident then made the traditional leaders agree that marpege-pege could also be done by the bride-to-be. Secondly, sipulut, which is the specialty food during marpege-pege, can be replaced with compote. This change was made by the customary king to maintain the health of the invited guests, especially the elderly who cannot consume sipulut because they have mag.